Microstructural Design of the Cast Iron via Laser Hardening with Defocused Beam of the Continuous Wave CO2 Laser. Issue 1 (1st May 2022) - Ahuir-Torres, J.I.; Sharp, M.; Bakradze, N.; Batako, A.D.L
Abstract: The cast iron is widely used in mechanical parts due to its good properties, as damping, good fluidity, resistance to deformation, excellent machinability and low cost. However, the number of its applications are reduced because its low corrosion, wear and friction resistance. The microstructure of the metallic materials has high influence on these properties. Laser hardening can improve these properties via designing of the microstructure. The evaluation of the laser parameter influence on the microstructural features is vital for a correct design of the microstructure and therefore, good improvement of the metallic material properties. Although the various laser parameter influence has been analysed on sundry papers, the influence of the distance from focal point and scan speed in the laser hardening microstructures has been rarely evaluated in the literature. Thus, the influence of this parameter on the microstructures generated through laser hardening is the subject matter of this work. The experiments were carried out with continuous wave carbon dioxide laser on samples of ground cast iron. The atmosphere was air flow at 0.7MPa, the laser operated at 100W and the scan rates were 1mm/s and 5mm/s. The distances to focal point of the laser beams ranged from 0.0mm to 5.6mm. The microstructures of the samples were revealed via nital and evaluated with optical microscopy. This work shown that the microstructure of gray iron cast can be designed by mean of laser hardening. In addition, laser hardened zones had various microstructures (e.g. austenitic, martensitic, pearlite and dendritic). The type of the microstructures in laser treated zones was determined by distance from focal point and scan speed. Moreover, the width and the depth of the laser hardened zones were generally enlarged with the increasing of the distance from focal point. Furthermore, the laser irradiation at slow rates, i.e. 1mm/s, produced laser hardened zones larger than laser scan at 5mm/s. In future works, the hardness, wear and friction resistance of the laser hardened samples will be evaluated because the literature review indicates that austenitic and martensitic microstructures show high values of these properties.